2016
DOI: 10.18632/oncotarget.13493
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ANXA3 is an independent prognostic indicator in gastric cancer and its depletion suppresses cell proliferation and tumor growth

Abstract: BackgroundGastric cancer (GC) is one of the most common malignancies worldwide. Tumour metastasis is one of the leading causes of death in GC patients. This study aims to investigate the significance of ANXA3 expression and the mechanism by which ANXA3 is involved in the epithelial–mensenchymal transition (EMT) of gastric cancer cells.ResultsOur results confirmed that ANXA3 was high expression at the mRNA and protein level in GC cancer tissues and the majority of GC cell lines. In clinicopathological analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Recent studies show that ANXA3 plays an important role in tumor growth and progression. Clinical evidence indicates that ANXA3 could be a potential biomarker of several types of cancers, such as bladder cancer, colon cancer and gastric cancer . It can also serve as an important marker for the invasion, the metastasis and the prognosis of breast cancer…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that ANXA3 plays an important role in tumor growth and progression. Clinical evidence indicates that ANXA3 could be a potential biomarker of several types of cancers, such as bladder cancer, colon cancer and gastric cancer . It can also serve as an important marker for the invasion, the metastasis and the prognosis of breast cancer…”
Section: Discussionmentioning
confidence: 99%
“…ANXA3 is highly expressed in gastric cancer tissue and cell lines, and overexpression of ANXA3 promoted cell proliferation and colony formation . Zhou et al reported that inhibition of ANXA3 suppressed the proliferation and invasion of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…ANXA3 has been demonstrated to function either as a tumor suppressor or promoter candidate in different types of cancer. Upregulation of ANXA3 enhances drug resistance and promotes tumor metastasis in breast cancer (47) and promotes tumor growth and predicts poor prognosis in gastric cancer (48), whereas in prostate cancer, ANXA3 protein expression is downregulated, which is associated with the tumor stage and Gleason score (49). In liver cancer, ANXA3 is upregulated and preferentially expressed in cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] Notably, a recent study also reported benefits of anti-ANXA3 monoclonal antibodies in a preclinical mouse model of HCC. 45 Although ANXA3 expression in many cancer cells seems to correlate directly with the rate of cellular proliferation, 47,48 the underlying mechanism(s) are undefined. We think that it might be worth investigating a possible role for ANXA3 in extending neutrophil longevitya phenomenon that has been observed during sepsis and is implicated in end-organ damage.…”
Section: Additional Reference Datasets Inform On Anxa3 Restriction Anmentioning
confidence: 99%